Operations excellence management system (OEMS) getting it right the first time - Lutchman, Chitram; Lutchman, Kevan; Ramakrishna, Akula; Lyons, Charles; Al Hashmi, Waddah Ghanem (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
Written for users, this book provides a structured approach with processes for implementing OEMS based on the learnings and experiences from companies who have implemented OEMS. The book leverages theknowledge of experienced OEMS personnel to provide a compelling sense of direction for organizations in the implementation of OEMS. The book includes sample templates and tools where necessary to ensure successful implementation and sustainment. The content of this book provides a testing methodology for implementing an OEMS across any organization while avoiding the pitfalls others have encountered along the way. The book: Provides a simple and easy process to follow for implementing an OEMS Offers organizations an opportunity to avoid the implementation errors of early adopters and provides them with the ability of learning from the experiences of others Equipped with tools and processes to make implementation and sustainment very effective, thereby avoiding false starts Designed to improve HSE, business reliability, efficiency, effectiveness, and performance on an ongoing basis Presents a simple pathway for helping organizations across all industries including those that operate within the various segments of the Oil and Gas business, to become more operationally disciplined in the way we do business and operate our assets in a high-risk operating environment
10 Business Unit (BU)/Function Implementation -- Focusing on Must-Haves and Known Gaps11 Auditing for Conformance and Compliance; 12 OEMS Implementation and Sustainment Software Platform; 13 Managing and Sustaining Performance; 14 Summary and Conclusions; Epilogue; Index
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Quality Control; TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / Industrial; Operations research; Management science